Medical Student’s Skills in Notifying Bad News Based on SPIKES Protocol - Azadi, Armin; Abdekhoda, Mohammadhiwa; Habibi, Shafi (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: This study was carried out to investigate the medical students’ skill in notifying bad news based on SPIKES. METHODOLOGY: The descriptive-analytic studywas conducted in which medical students of Tabriz University of Medical Sciences were participated. To collect data, a two-part questionnaire was used, included 18 questions about how bad news were communicated, and 40 questions based on scenarios of students’ skills with bad news communication according to the SPIKES step protocol. Data were analyzed using SPSS software and independent T-test. RESULTS: The findings showed that students had the most proficiency in the fifth step of the SPIKES (recognizing and expressing sympathy with patient), and the least skill in the 3rdphase of the SPIKES (examining the patient’s readiness to receive all or part of the news). A statistical significant difference between skill and performance based on work experiences was observed (F=3.98, P=0.02). However, the data show no significant difference between skill and performance based on characteristic factors i.e. age and gender. CONCLUSION: According to the SPIKES, students’ skills in informing “Bad News” are not at an optimal level. They did not receive the necessary training to notify bad news. Sophisticated students, with more work experience have more skill in informing “Bad News”. The training of the “Bad News” informing skills should be on focus to education professionals.